Laparoscopic mesh sacrohysteropexy with concurrent laparoscopic myomectomy for treatment of multiple myomas: Case report and literature review - Orawee Chinthakanan (2018)
Conservative surgical management of uterine prolapse with uterine conservation has become an alternative treatment in women who wish to maintain their uterus. Vaginal and abdominal approaches for uterine suspension have been described and reported. Certain concomitant pathologic conditions of the uterus such as uterine myomas have been considered in some patients to be a contraindication to conservative surgery. Herein we report the case of a 55-year-old woman with symptomatic uterine prolapse with multiple myomas who desired uterine preservation and was successfully treated via laparoscopic myomectomy and laparoscopic mesh sacrohysteropexy. © 2013 AAGL.